On tasty colours and colourful tastes? Assessing, explaining, and utilizing crossmodal correspondences between colours and basic tastes - Spence, C; Wan, X; Woods, A; Velasco, C; Deng, J; Youssef, J; Deroy, O (BioMed Central, 2015)
Can basic tastes, such as sweet, sour, bitter, salty, and possibly also umami, be conveyed by means of colour? If so, how should we understand the relationship between colours and tastes: Is it universal or relative, innate or acquired, unidirectional or bidirectional? Here, we review the growing body of scientific research showing that people systematically associate specific colours with particular tastes. We highlight how these widely shared bidirectional crossmodal correspondences generalize across cultures and stress their difference from synaesthesia (with which they are often confused). The various explanations that have been put forward to account for such crossmodal mappings are then critically evaluated. Finally, we go on to look at some of the innovative ways in which chefs, culinary artists, designers, and marketers are taking—or could potentially push further—the latest insights from research in this area as inspiration for their own creative endeavours.